A Bézier extraction based XIGA approach for three-dimensional crack simulations. (November 2018) - Singh, S.K.; Singh, I.V.; Bhardwaj, G.; Mishra, B.K.
Highlights: Bézier extraction based XIGA approach is successfully implemented for the analysis of 3-D crack problems. SIFs for 3-D cracks are evaluated by interaction integral approach using virtual cuboidal domain. Auxiliary fields used in the interaction integral are obtained approximately in terms of level set functions. Higher-order continuity of NURBS basis functions produces smooth variation of level set functions. Results obtained by Bézier extraction based XIGA are found in good agreement with XFEM and analytical solutions. Abstract: In this work, Bézier extraction based extended isogeometric analysis (XIGA) has been performed for three-dimensional (3-D) crack simulations in linear elastic materials. The Bézier extraction represent the original NURBS basis functions in terms of Bernstein shape functions defined over C  0 continuous isogeometric Bézier elements, and provides an element wise data structure of NURBS which makes the implementation similar to extended finite element method (XFEM). A crack in the domain is modeled by Heaviside and crack tip enrichment functions. The values of mixed-mode stress intensity factors (SIFs) are obtained by interaction integral approach using virtual cuboidal domain. Various 3-D crack problems are solved by Bézier extraction based XIGA, and the results are compared with XFEM and analytical solutions.